2005
DOI: 10.1079/bjn20041355
|View full text |Cite
|
Sign up to set email alerts
|

Application of inulin-type fructans in animal feed and pet food

Abstract: The inulin-type fructans are non-digestible oligosaccharides that are fermented in the gastrointestinal tract of farm animals and pets. This review focuses on the various effects of inulin-type fructans in pigs, poultry, calves and companion animals. Effects of the inulin-type fructans on gut microflora, digestion and availability of nutrients, gut morphology, fermentation characteristics and animal performance are discussed. Inulin-type fructans can support animal performance and health by affecting nutrient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
1
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(67 citation statements)
references
References 45 publications
3
59
1
4
Order By: Relevance
“…The metabolism of anaerobic bacteria present in the cecum of birds increases the concentration of organic acids, such as butyric acid, exerting a protective effect against the presence of certain pathogens. VERDONK et al (2005) reinforce the hypothesis that the protective action of prebiotics, as well as resistance to infections, varies according to the type and dose of inulin for each species, and also the virulence of the investigated agent. In this case, there was no protection against S. Enteritidis infection with treatment protocol restricted to the first days of breeding.…”
Section: Age (Weeks)supporting
confidence: 62%
“…The metabolism of anaerobic bacteria present in the cecum of birds increases the concentration of organic acids, such as butyric acid, exerting a protective effect against the presence of certain pathogens. VERDONK et al (2005) reinforce the hypothesis that the protective action of prebiotics, as well as resistance to infections, varies according to the type and dose of inulin for each species, and also the virulence of the investigated agent. In this case, there was no protection against S. Enteritidis infection with treatment protocol restricted to the first days of breeding.…”
Section: Age (Weeks)supporting
confidence: 62%
“…Inulin consists of a mixture of fructan chains (Flickinger et al, 2003) and is one of the most studied prebiotic sources in domestic animals (Castellini et al, 2007). In humans and rodents, inulin selectively stimulates lactobacilli and bifidobacteria in the large intestine (LI; Gibson et al, 2004), whereas the effect on the microbiota in pigs is less clear and varies between studies (Verdonk et al, 2005). A recent study in weaning piglets has shown that inulin in combination with benzoic acid increased the bacterial diversity in digesta, whereas inulin alone decreased the relative abundance of Lactobacillus acidophilus and tended to increase the relative abundance of Megasphaera elsdenii (Halas et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The divergence in productivity response of broilers to dietary inulintype fructans may be caused by several factors, like type of fructans and their inclusion level, composition of the basal diet, animal characteristics and experimental hygiene conditions (i.e. stress factors) (Hussein et al, 1998;Lan et al, 2007;Patterson and Burkholder, 2003;Van Loo, 2007;Verdonk et al, 2005;Yang et al, 2008).…”
Section: Effect Of Dietary Fructans On Growth Performance and Dietarymentioning
confidence: 99%